Asymptomatic coronary aneurysms in a patient with eosinophilic granulomatosis with polyangiitis who developed a digital gangrene. (2nd January 2021) - Sato, Mayu; Yoshida, Yusuke; Sugimoto, Tomohiro; Kishimoto, Shinji; Omoto, Takuji; Watanabe, Hirofumi; Tokunaga, Tadahiro; Yukawa, Kazutoshi; Kohno, Hiroki; Mokuda, Sho; Nojima, Takaki; Hirata, Shintaro; et al.
Abstract: A 33-year-old male with a history of bronchial asthma and allergic rhinitis was diagnosed with eosinophilic granulomatosis with polyangiitis (EGPA) eight years ago. The diagnosis was based on the presence of fever, remarkable eosinophilia, and painful digital ulcer. His signs and symptoms improved with a moderate dose of glucocorticoids. Thereafter, he was lost to follow-up, failing to attend any of the scheduled appointments. Three years later, he presented with painful digital gangrene on the lateral fold of the right ring fingernail and abdominal pain triggered by meals. Angiography showed multiple occlusions and severe stenoses of the peripheral arteries and coronary aneurysms, which confirmed the diagnosis of medium vessel vasculitis of the coronary and peripheral arteries due to flare up of EGPA. EGPA predominantly affects the small-sized vessels, but rarely the medium-sized vessels. Coronary vasculitis might occur asymptomatically, until the coronary stenosis becomes severe or myocardial infarction develops; hence, its prevalence is underestimated. In this case, a digital gangrene prompted us to perform a systemic angiography, leading to the diagnosis of coronary vasculitis. Careful observation for coronary lesions is necessary in patients with EGPA who develop digital gangrene.